CARD11 regulates the thymic Treg development in an NF-κB-independent manner - Hu, Yu; Han, Lingli; Xu, Wenwen; Li, Tianci; Zhao, Qifan; Lu, Wei; Sun, Jinqiao; Wang, Ying (Frontiers in Immunology, 2024)
CARD11 is a lymphoid lineage-specific scaffold protein regulating the NF-B activation downstream of the antigen receptor signal pathway. Defective CARD11 function results in abnormal development and differentiation of lymphocytes, especially thymic regulatory T cells (Treg). By applying transgenic mouse models carrying pathogenic mutations from patients, we found CARD11 mutations causing hyper-activated NF-B signals also gave rise to compromised Treg development in the thymus, similar to the phenotype in Card11 deficient mice. This observation challenges the previous view that CARD11 regulates Treg lineage dependent on the NF-B activation. Mechanistic investigations reveal that the noncanonical function CARD11, which negatively regulates the AKT/FOXO1 signal pathway, is responsible for regulating Treg generation. Moreover, primary immunodeficiency patients carrying CARD11 mutation, which autonomously activates NF-B, also represented the reduced Treg population in their peripheral blood. Our results propose a new regulatory function of CARD11 and illuminate an NF-B independent pathway for thymic Treg lineage commitment.